ABCB1 (P‐glycoprotein) regulates vitamin D absorption and contributes to its transintestinal efflux. Issue 2 (17th September 2018) - Margier, Marielle; Collet, Xavier; le May, Cédric; Desmarchelier, Charles; André, François; Lebrun, Chantal; Defoort, Catherine; Bluteau, Alice; Borel, Patrick; Lespine, Anne; Reboul, Emmanuelle
ABSTRACT: Efficient intestinal absorption of dietary vitamin D is required in most people to ensure an adequate status. Thus, we investigated the involvement of ATP binding cassette subfamily B member 1 (ABCB1) in vitamin D intestinal efflux. Both cholecalciferol (D3 ) and 25‐hydroxycholecalciferol [25(OH)D3 ] apical effluxes were decreased by chemical inhibition of ABCB1 in Caco‐2 cells and increased by ABCB1 overexpression in Griptites or Madin‐Darby canine kidney type II cells. Mice deficient for the 2 murine ABCB1s encoded by Abcb1a and Abcb1b genes ( Abcb1 −/− ) displayed an accumulation of 25(OH)D3 in plasma, intestine, brain, liver, and kidneys, together with an increased D3 postprandial response after gavage compared with controls. 25(OH)D3 efflux through Abcb1 −/− intestinal expiants was markedly decreased compared with controls. This reduction of 25(OH)D3 transfer from plasma to lumen was further confirmed in vivo in intestine‐perfused mice. Docking experiments established that both D3 and 25(OH)D3 could bind with high affinity to Caenorhabditis elegans P‐glycoprotein, used as an ABCB1 model. Finally, in a group of 39 healthy male adults, a single‐nucleotide polymorphism (SNP) in ABCB1 (rs17064) was significantly associated with the fasting plasma 25(OH)D3 concentration. Thus, we showed here for the first time that ABCB1 is involved in neo‐absorbed vitamin D efflux by the enterocytes and that it also contributes to vitamin D transintestinal excretion and likely impacts vitamin D status.—Margier, M., Collet, X., leMay, C., Desmarchelier, C., André, F., Lebrun, C., Defoort, C., Bluteau, A., Borel, P., Lespine, A., Reboul, E. ABCB1 (P‐glycoprotein) regulates vitamin D absorption and contributes to its transintestinal efflux. FASEB J. 33, 2084–2094 (2019). www.fasebj.org